Ernest Joseph King papers - King, Ernest Joseph, 1878-1956.; King, Ernest Joseph, 1878-1956.
Correspondence, memoranda, speeches, writings, notes, orders to duty, printed matter, photographs, and other papers relating primarily to King's activities as commander in chief of the U.S. Fleet and chief of naval operations during World War II. Documents his participation in Allied conferences including the Argentina Conference (August 1941), Quebec Conference (1943), Cairo Conference (1943), Teheran Conference (1943), Yalta Conference (1945), and Potsdam Conference (July 1945). Also documents his service as commander of the Submarine Base in New London, Conn.; chief of the U.S. Navy Dept. Bureau of Aeronautics; commander of the Aircraft Base and Aircraft Scouting Force in San Diego, Calif.; and commander of all aircraft carriers of the fleet. Subjects include salvaging of the S-51 sunk off Block Island in 1925; growth and development of military aviation; the Atlantic Charter; World War II naval strategy in the Pacific including the Battle of Guadalcanal, Solomon Islands, (1942-1943), and General James Harold Doolittle's 1942 air raid on Tokyo; international control of atomic weapons; U.S. Joint Chiefs of Staff; national security; and world politics. Includes drafts of Fleet Admiral King; A Naval Record (1952) coauthored by King and Walter Muir Whitehill.
Correspondents include Henry Harley Arnold; C.R. Attlee; Bernard M. Baruch; Omar Nelson Bradley; Oliver Lyttelton, Viscount Chandos; Mark W. Clark; Ferdinand Eberstadt; Charles A. Edison; Merritt Austin Edson; Richard S. Edwards; Dwight D. Eisenhower; Douglas Southall Freeman; William Frederick Halsey; Cordell Hull; Charles Frederick Algernon Portal, Viscount Portal of Hungerford; Frank Knox; P.W. Litchfield; George C. Marshall; Louis Mountbatten, Earl Mountbatten of Burma; Chester W. Nimitz; Quentin James Reynolds; Franklin D. Roosevelt; Robert E. Sherwood; Dorothy Thompson; Harry S. Truman; Walter Muir Whitehill; and Orville Wright.
Naval officer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Naval Historical Foundation collection.
Keywords: Arnold, Henry Harley, -- 1886-1950 -- Correspondence; Attlee, C. R. -- 1883-1967 -- Correspondence; Baruch, Bernard M. -- 1870-1965 -- Correspondence; Bradley, Omar Nelson, -- 1893-1981 -- Correspondence; Chandos, Oliver Lyttelton, -- Viscount, -- 1893-1972 -- Correspondence; Clark, Mark W. -- 1896-1984 -- Correspondence; Doolittle, James Harold, -- 1896-1993.; Eberstadt, Ferdinand -- Correspondence; Edison, Charles A., -- 1890-1969 -- Correspondence; Edson, Merritt Austin, -- 1897-1955 -- Correspondence; Edwards, Richard S. -- 1885-1956 -- Correspondence; Eisenhower, Dwight D. -- 1890-1969 -- Correspondence; Freeman, Douglas Southall, -- 1886-1953 -- Correspondence; Halsey, William Frederick, -- 1882-1959 -- Correspondence; Hull, Cordell, -- 1871-1955 -- Correspondence; Hungerford, Charles Frederick Algernon Portal, -- Viscount Portal of, -- 1893-1971 -- Correspondence; Knox, Frank, -- 1874-1944 -- Correspondence; Litchfield, P. W. -- 1875-1959 -- Correspondence; Marshall, George C. -- 1880-1959 -- Correspondence; Mountbatten of Burma, Louis Mountbatten, -- Earl, -- 1900-1979 -- Correspondence; Nimitz, Chester W. -- 1885-1966 -- Correspondence; Reynolds, Quentin James, -- 1902-1965 -- Correspondence; Roosevelt, Franklin D. -- 1882-1945 -- Correspondence; Sherwood, Robert E. -- 1896-1955 -- Correspondence; Thompson, Dorothy, -- 1893-1961 -- Correspondence; Truman, Harry S., -- 1884-1972 -- Correspondence; Whitehill, Walter Muir, -- 1905-1978 -- Correspondence; Wright, Orville, -- 1871-1948 -- Correspondence; United States. -- Joint Chiefs of Staff; United States. -- Navy -- History -- World War, 1939-1945.; United States. -- Navy -- Submarine forces; United States. -- Navy Department. -- Bureau of Aeronautics; United States. -- Navy. -- U.S. Fleet; Allied and Associated Powers (1914-1920); Atlantic Charter -- (1941); Guadalcanal, Battle of, Solomon Islands, 1942-1943.; Aeronautics, Military -- United States; Atomic bomb; International relations; National security -- United States; Navy-yards and naval stations -- California -- San Diego; Navy-yards and naval stations -- Connecticut -- New London; Nuclear arms control; Nuclear weapons; Submarines (Ships) -- Salvaging; Security, International; World politics; World War, 1939-1945 -- Aerial operations, American; World War, 1939-1945 -- Campaigns -- Pacific Area; World War, 1939-1945 -- Congresses; World War, 1939-1945 -- Diplomatic history; World War, 1939-1945 -- Naval operations, American; World War, 1939-1945 -- Peace; Tokyo (Japan) -- History -- Bombardment, 1942.; Naval officers